Carga de trabajo de la enfermera en la unidad de cuidados intensivos. Hospital Regional Lambayeque - Vásquez Acosta, Diana Patricia (2017)
A cross – sectional descriptive study was carried out in March 2015, whose objective was to identify the level of the nurse´s workload measured by the TISS-28 and NAS scales in the Intensive Care Unit (ICU) of the Regional Lambayeque Hospital. Data were collected from the sample universe consisting of 15 nurses, obtaining a total of 60 measurements with each one of the TISS-28 and NAS scales, the same ones were consolidated in 30 measurements with TISS-28 of 24-hour scale and 30 measurements with NAS scale of 24 hours. It was concluded that the level of workload of nurses according to the TISS-28 was 53.33% of nurses had a “medium” workload level, 46.67% of nurses had a load level of high work, and no nurse had “low” workload. The level of workload of nurses according to the NAS was 93.33% of nurses had a “high” workload level, 6.67% of nurses had a “medium” workload level and no nurse had workload “under”.